Biogeomorphic aspects of lichen colonisation in part of western Dronning Maud Land, Antarctica - Ayres, Gabrielle Alexzena (Rhodes University, Faculty of Science, Department of Geography, 2017)
Ice-free regions in Antarctica provide natural laboratories for investigating and modelling change in landscapes and ecosystems. The terrestrial ecosystems in western Dronning Maud Land are potentially critical to improve current understanding of polar ecosystems, however, they remain poorly represented and under-protected. Lichen habitats were used to elucidate geomorphic-biological feedbacks that shape the landscape's topography and biodiversity, which in turn promote environmental heterogeneity. Environmental parameters acting on two landforms were measured to determine the colonisation and growth of lichens in niche habitats. The habitats were identified and characterised, and topographic heterogeneity was found to control lichen colonisation. Micro-topographical niches provide the most stable environments for colonisation, and are preferred habitats. Lichen-habitat interactions were species specific, and closely related to insolation and moisture availability. The bidirectional relationships between rock weathering and lichen colonisation was ascertained. Results showed that lichens are good indicators of landform heterogeneity, but also promote landform heterogeneity. Given the habitat preferences of specific lichen species, they provide proxy to evaluating environmental responses, especially environmental change. The findings of this research are to be used as baseline data for future studies exploring ecosystem development in emerging landforms.
Keywords: Lichen communities -- Queen Maud Land; Lichens -- Ecology -- Queen Maud Land; Polar regions; Ecology -- Polar regions; Antarctica; Ecology -- Antarctica